Estudio de calidad de vida 2004. Municipio de Medellín (2004)
ABSTRACT: The report gives an account of aspects related to the different stages developed to ensure the implementation of the project Quality of Life Survey for 2004 Medellin. It is a relationship of the formation of work teams and the process used to ensure the collection and processing of information.